Design, modification, and bio-evaluation of salazinic acid derivatives - Nguyen-Kim-Tuyen Pham (Elsevier, 2022)
Data on synthesized derivatives of salazinic acid are scarce, with existing reports addressing only derivative hexaacetyl salazinic acid. This study investigated a set of novel potential antidiabetic agents. Analogs of salazinic acid were designed and synthesized using bromination, nucleophilic addition, Friedel-Crafts alkylation, and esterification. Ten synthetic compounds were prepared and structurally elucidated, including eight new compounds (1a-1c, 2a, 3a, 3b, 4a, 4b) and two known analogs. Under bromination, salazinic acid (1) enabled the following reaction chain: oxidation, decarboxylation, and substitution. This yielded products 1a-1c, which were found to have unprecedented scaffolds. Parmosidone F (5) was prepared from 1 with orsellinic acid via Friedel-Crafts alkylation, confirming a previously reported biosynthesis route. These analogs were evaluated for enzyme inhibition of α-glucosidase, and all showed more potent activity than that of acarbose, a positive control (IC50 332 μM), with IC50 values in the range 9.32–39.96 μM. An in silico molecular docking model confirmed that, in terms of enzyme inhibition, the compounds ranked as follows: 3b > 4b > 4a > 1c > 2a > 1b > 1a > 3a. The kinetics of enzyme inhibition showed 4a and 5 to be a non-competitive-type and mixed-type inhibitors, respectively.